Design of Intelligent Mobile Vehicle Checking System Based On ARM 7 (International Journal of Engineering and Computer Science, 2014)
With ARM 7 as the core, the new Intelligent Mobile Vehicle Checking System integrated with a lot of hardware & software module such as image capturing, number plate recognition, GSM, GPS etc. the design of the system software used the embedded software developing platform as Keil, met the traffic auditing department’s needs about Mobile Vehicle Checking.